Learning Governance Strategy in Improving the Quality of Education: A Study at SD Negeri 1 Simeulue Cut Aceh - Tauhid Harsami; Nasir Usman; Niswanto Niswanto; Markas Afaidi (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This research is motivated by the low quality of primary education in the archipelago, particularly at SD Negeri 1 Simeulue Cut, which is influenced by suboptimal learning governance. The purpose of this study is to explain the strategy of curriculum governance and learning planning, classroom governance and ICT-based teacher-student interaction, and teacher career development governance through learning communities. The methodology used is descriptive qualitative with interview, observation, and documentation techniques, as well as data analysis using the Miles and Huberman model. The research was conducted at SD Negeri 1 Simeulue Cut for three months, involving the principal, teachers, and students as participants. The results show that teachers have prepared lesson plans and teaching materials according to standards, utilized contextual media, and began to integrate ICT in learning. The teacher learning community has also been shown to encourage the development of professionalism and innovation. In conclusion, curriculum governance, ICT-based interaction, and an integrated teacher community contribute significantly to improving the quality of education in elementary schools. This study contributes to the development of an integrated learning governance model based on curriculum, ICT, and teacher communities in an effort to improve the quality of primary education.